Analysis of the influences of social isolation on cognition and the therapeutic potential of deep brain stimulation in a mouse model - Hu, Yun-Yun; Ding, Xuan-Si; Yang, Gang; Liang, Xue-Song; Feng, Lei; Sun, Yan-Yun; Chen, Rui; Ma, Quan-Hong (Frontiers in Psychiatry, 2023)
Social interaction is a fundamental human need. Social isolation (SI) can have negative effects on both emotional and cognitive function. However, it is currently unclear how the age and duration of SI affects emotion and recognition function. There is also no specific treatment for the effects of SI. In this study, we investigated the effects of SI on behavior in mice of different age groups and durations of SI through a series of behavioral tests, including three-chamber social experiments, and explored the possible underlying mechanisms through techniques such as immunofluorescence staining. We found that social recognition was affected in the short term, while social preference was damaged by extremely long periods of SI. In addition to affecting social memory, SI also affects emotion, short-term spatial ability and learning motivation in mice. Myelin decreased significantly in the medial prefrontal cortex (mPFC) and dorsal hippocampus of socially isolated mice. At the same time, we found neuronal activation disorders in mPFC and dorsal hippocampus of mice that experienced SI after social behavior stimulation. DBS is a therapeutic method that directly delivers electrical currents to specific brain regions and may modulate pathological activity of various brain circuits. Studies have shown that DBS applied to relevant circuit nodes relieves cognitive impairment by activating neurons and promoting the release of certain region-specific neurotransmitters. In this study, by stimulating mPFC using DBS, we found that DBS relieved neuronal activation disorders in mPFC after long-term SI and improved social preference in mice.